Has the increased participation in the national campaign 'Dry January' been associated with cutting down alcohol consumption in England?. (1st October 2021) - Case, Philippa; Angus, Colin; De Vocht, Frank; Holmes, John; Michie, Susan; Brown, Jamie
Highlights: Dry January was not associated with large population-level declines in alcohol consumption. People were more likely to cite Detox (e.g., Dry January) as a motive in a quit attempt in January. The proportion of people citing Detox (e.g., Dry January) throughout the year as a reason for a quit attempt increased between 2014 and 2018. Abstract: Aims: Dry January is a national multimedia campaign in the UK that encourages people to abstain from drinking alcohol during the month of January. The population-level campaign makes extensive use of email and social media to support participants and has reported a substantial increase in participation since 2015. This study aimed to assess whether the increase in participation in Dry January between 2015 and 2018 was associated with reduced alcohol consumption in England. Design: Repeat cross-sectional design. Setting: England, March 2014 to January 2018. Participants: A total of 37, 142 respondents to the Alcohol Toolkit Study, a monthly in-home survey of alcohol consumption among representative cross-sectional samples of people aged 16+ years in England. Measures: Outcomes included i) percentage of adults reporting drinking monthly or less frequently in the last 6 months and ii) mean weekly alcohol consumption among drinkers derived from the Alcohol Use Disorders Identification Test questions on typical frequency and quantity in the last 6 months. Analyses: For each outcome, regression models were fitted for month: January (2015 and 2018) vs March-December (2014 and 2017) and for year: 2014/15 vs 2017/18. Interaction terms were included in the models to examine whether the difference between January and the preceding months on each outcome measure depended upon the year (2014/15 vs 2017/18). For non-significant interactions, Bayes factors were calculated to assess the relative strength of evidence for large effects (OR = 1.80 on monthly drinking and β=-1.0 on mean consumption) compared with the null. Results: Differences between January and other months were similar in 2014/15 and 2017/18 for adults reporting drinking monthly or less frequently and the mean consumption among drinkers (OR = 0.91, 95 %CI 0.79–1.05, BF = 0.05; β = 0.55, 95 %CI=-0.14 to 1.25, BF = 0.13 respectively). Conclusions: The increase in participation in Dry January between 2015 and 2018 was not associated with large corresponding changes in people drinking monthly or less frequently over the last 6 months, or in mean weekly consumption among drinkers.